Exile Poems of Mahroso Doloh: Voices From Foreign Land in Kiblat Cinta-Kumpulan Sajak Suara Bunga Patani: (Puisi Exile Mahroso Doloh: Suara dari Tanah Asing dalam Kiblat Cinta-Kumpulan Sajak Suara Bunga Patani) (Malay Literature, 2019)
Exile is a term of isolation, which involves the author or his work produced in a state of exile, either in a new place of emigration or in his native land. Exile may be voluntary, or be the result of economic, political, legal or military pressures. Because the term covers a broad range of meaning, it the term exile'is maintained here in its original form to discuss a number of poems written by Mahroso Doloh in his poetry collection entitled Kiblat Cinta-Kumpulan Sajak Suara Bunga Patani. This study explains the meaning of exile through the perspective of several scholars, and discusses its appearance in Mahroso Doloh's poems through two topics, namely the response of the exiled author, and the experience of the exiled author. The result is the finding of what exile literature is and how exile literature is used by exiled authors to obtain relief or tranquillity, whether in the land they have emigrated to, or their homeland.Keywords: exile, statelessness, outcast, homeland, immigration country